PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MENGGUNAKAN APLIKASI MOODLE PADA MATA KULIAH METROLOGI INDUSTRI PROGRAM STUDI D3 TEKNIK MESIN UNIVERSITAS NEGERI JAKARTA - Sri Rahayu (LPPM, Universitas Negeri Jakarta, 2021)
This study aims to improve learning outcomes for Industrial Metrology courses by applying the Blended Learning learning model using the web-based Moodle Application for students of the D3 Mechanical Engineering Study Program, Jakarta State University semester 111 (Odd 2019/2019). The method used in this research is Classroom Action Research (CAR) which is a form of investigation carried out by participants involved in the situation under study. Implementation of actions followed by observation and reflection activities. If necessary, at the next stage, a follow-up plan is drawn up. These efforts are carried out in a cycle to form a cycle. The place of research was conducted at the State University of Jakarta and the research subjects were 29 students of D3 Mechanical Engineering class B. This research was conducted from November 7, 2019 to December 19, 2019. Data on learning outcomes were obtained through a written test and then analyzed to compare the results of the exam in each cycle. The results of this study indicate that there is an increase in student learning outcomes in the Industrial Metrology course by applying a blended learning model using the Moodle application. The increase in learning outcomes can be seen where in the first cycle student learning outcomes with an average of 60, 11 students completed or 37.9% and 18 students have not completed or 62.1%. While in cycle II there was an increase in student learning outcomes, with an average of 77.5, 27 students completed or 93.1% and 2 students did not complete or 6.9% Researchers can conclude that student learning outcomes have increased by applying the Blended Learning learning model using the application Moodle. Keywords: blended learning, moodle, learning outcomes, classroom action research, industrial metrology